2018
DOI: 10.1155/2018/8938597
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Shiga Toxigenic Escherichia coli O157:H7 Infection from Raw and Fermented Milk in Sokoto Metropolis, Nigeria

Abstract: Escherichia coli O157:H7 is an enteric foodborne pathogen associated with life threatening disease conditions. The enterobacteria are frequently found in cattle gastrointestinal tract with high potential of contaminating animal products such as meat, milk, and cheese. A cross-sectional study was conducted to investigate the presence of Shiga toxin-producing Escherichia coli O157:H7 in milk products sold within Sokoto metropolis. Two hundred and sixty (260) samples (comprising 160 raw and 100 fermented milk sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
9

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 23 publications
(23 reference statements)
3
16
9
Order By: Relevance
“…The present study revealed an overall E. coli prevalence of 54.7% from different foods of bovine origin collected from different sources in the study areas. This prevalence was in agreement with previous studies reported by Limbu et On the other hand, the prevalence of E. coli in the current study was higher than the reports of Messele et al [7] in Addis Ababa and Bishoftu towns (5.5%), Messele et al [12] in central Ethiopia (Sebeta, Burayu, and Holeta towns) (7.1%), Kumar and Prasad [69] in and around Pantnagar (India) (8.14%), Yakubu et al [70] in Sokoto Metropolis (Nigeria) (9.23%), Mengistu et al [71] in Eastern Ethiopia (12.41%), Ngaywa et al [72] in Kenya (13.8%), Mohammed et al [73] in Dire Dawa city (15.89%), Ababu et al [17] in Holeta District (19.0%), Hiwot et al [74] in Arsi and East Shewa Zones (19.8%), Bedasa et al [19] in Bishoftu town (20.0%),…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present study revealed an overall E. coli prevalence of 54.7% from different foods of bovine origin collected from different sources in the study areas. This prevalence was in agreement with previous studies reported by Limbu et On the other hand, the prevalence of E. coli in the current study was higher than the reports of Messele et al [7] in Addis Ababa and Bishoftu towns (5.5%), Messele et al [12] in central Ethiopia (Sebeta, Burayu, and Holeta towns) (7.1%), Kumar and Prasad [69] in and around Pantnagar (India) (8.14%), Yakubu et al [70] in Sokoto Metropolis (Nigeria) (9.23%), Mengistu et al [71] in Eastern Ethiopia (12.41%), Ngaywa et al [72] in Kenya (13.8%), Mohammed et al [73] in Dire Dawa city (15.89%), Ababu et al [17] in Holeta District (19.0%), Hiwot et al [74] in Arsi and East Shewa Zones (19.8%), Bedasa et al [19] in Bishoftu town (20.0%),…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, the prevalence of E. coli in the current study was higher than the reports of Messele et al [7] in Addis Ababa and Bishoftu towns (5.5%), Messele et al [12] in central Ethiopia (Sebeta, Burayu, and Holeta towns) (7.1%), Kumar and Prasad [69] in and around Pantnagar (India) (8.14%), Yakubu et al [70] in Sokoto Metropolis (Nigeria) (9.23%), Mengistu et al [71] in Eastern Ethiopia (12.41%), Ngaywa et al [72] in Kenya (13.8%), Mohammed et al [73] in Dire Dawa city (15.89%), Ababu et al [17] in Holeta District (19.0%), Hiwot et al [74] in Arsi and East Shewa Zones (19.8%), Bedasa et al [19] in Bishoftu town (20.0%), Sebsibe and Asfaw [75] in Jimma town (20.2%), Tadese et al [76] in Ambo town (23.4%), Abebe et al [77] in selected districts of Tigray (23.7%), Abayneh et al [78] in Jimma town (23.9%), Yohannes [79] in Mekelle town (25.0%), Haileselassie et al [80] in Mekelle city (27.3%), Hiko et al [81] in Addis Ababa (29.0%), Momtaz et al [82] in Iran (29.7%), Taye et al [83] in Haramaya University abattoir (30.97%), Disassa et al [8] in and around Asosa town (33.9%), Tadesse et al [53] in Mekelle town (36.63%), Thaker et al [84] in Anand Gujarat (India) (38.0%), Zerabruk et al [85] in Addis Ababa (43.75%), Sobeih et al [86] in Kafr El-Sheikh Governorate (Egypt) (44.44%), and Welde et al [87] in and around Modjo town (46.26%).…”
Section: Discussioncontrasting
confidence: 72%
“…In a study from Nigeria, 260 raw and fermented milk samples had an E. coli detection rate of 9.23% (24/260), of which five (20.83%) were positive for O157: H7. The overall incidence of E. coli O157: H7 was therefore 1.92% (Yakubu, Shuaibu, Ibrahim, Hassan, & Nwachukwu, 2018). Also in Nigeria, 10 out of 202 (5%) dairy samples were positive for serotype O157: H7, including one from 50 milk samples (2%), three from 50 samples of fresh local cheese (6%), one from 50 samples of fried local cheese (2%), and five from 52 fermented milk samples (9.6%) (Ivbade, Ojo, & Dipeolu, 2014).…”
Section: Discussionmentioning
confidence: 96%
“…Among the microorganisms present in fermented milk are strains of E. coli . A study by Yakubu et al (2018) showed the presence of the most pathogenic serotype E. coli O157: H7 in samples of this product from 100 points of sale in the area of Nigeria. The main source of E. coli strains, including those with a high pathogenic potential, is the gastrointestinal tract of cattle (animals do not show clinical signs of infection).…”
Section: Dairy Productsmentioning
confidence: 94%